2007
DOI: 10.1016/j.neuron.2007.01.034
|View full text |Cite
|
Sign up to set email alerts
|

A Subset of Dorsal Neurons Modulates Circadian Behavior and Light Responses in Drosophila

Abstract: A fundamental property of circadian rhythms is their ability to persist under constant conditions. In Drosophila, the ventral Lateral Neurons (LNvs) are the pacemaker neurons driving circadian behavior under constant darkness. Wild-type flies are arrhythmic under constant illumination, but flies defective for the circadian photoreceptor CRY remain rhythmic. We found that flies overexpressing the pacemaker gene per or the morgue gene are also behaviorally rhythmic under constant light. Unexpectedly, the LNvs do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
140
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(158 citation statements)
references
References 43 publications
18
140
0
Order By: Relevance
“…Grima et al, 2004), previous reports suggest that the molecular oscillations in DN1 neurons play an important role in determining rhythmic activity/rest behavior both under DD and LL conditions (de la Paz Fernandez et al, 2007;Murad et al, 2007). The results of a study which manipulated molecular oscillations in circadian pacemaker circuit by targeted expression of SHAGGY (SGG; a clock component whose overexpression speeds up the oscillations in mRNA of circadian genes) (Stoleru et al, 2005) suggests that whereas sLNv, LNd, DN1, and DN3 cells are part of a circuit that regulates locomotor activity rhythm, the lLNv and DN2 cells form a separate and independent circuit that apparently does not influence locomotor activity rhythm and that the DN2 cells are the dominant component of this second circuit and regulate the oscillations in the lLNv (Stoleru et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Grima et al, 2004), previous reports suggest that the molecular oscillations in DN1 neurons play an important role in determining rhythmic activity/rest behavior both under DD and LL conditions (de la Paz Fernandez et al, 2007;Murad et al, 2007). The results of a study which manipulated molecular oscillations in circadian pacemaker circuit by targeted expression of SHAGGY (SGG; a clock component whose overexpression speeds up the oscillations in mRNA of circadian genes) (Stoleru et al, 2005) suggests that whereas sLNv, LNd, DN1, and DN3 cells are part of a circuit that regulates locomotor activity rhythm, the lLNv and DN2 cells form a separate and independent circuit that apparently does not influence locomotor activity rhythm and that the DN2 cells are the dominant component of this second circuit and regulate the oscillations in the lLNv (Stoleru et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…In this case, molecular oscillation appears to persist in DN1 up to the fourth day in LL as quantified by cell counts based on PDP-1 staining (Murad et al, 2007). The peak in PDP-1-immunopositive cell numbers coincides with falling levels of locomotor activity (although not the trough) (Murad et al, 2007). Two simultaneously occurring behavioral rhythms are seen in LL in cry b mutants, with increasing fraction of flies showing polyrhythmic locomotor behavior with increasing light intensity (Yoshii et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although LN v s are sufficient to drive rest:activity rhythms in constant darkness (DD) and set the period of the clock, robust behavioral and physiological rhythms are an emergent property of the clock network as a whole (Peng et al 2003;Guo et al 2014;Yao and Shafer 2014;Roberts et al 2015;Liang et al 2016). LN d s and DN1 neurons are targets of PDF and play roles in regulating multiple features of circadian behavior, including rhythm strength, phase, and circadian period (Murad et al 2007;Lear et al 2009;Zhang et al 2010;Guo et al 2014).…”
mentioning
confidence: 99%
“…Genetic studies in Drosophila have identified CRYPTOCRHOME (CRY), a protein photopigment essential for circadian photoentrainment. They have also identified anatomically distinct clock neurons, evening cells (E cells) and morning cells (M cells), as the key pacemakers timing the onset of the evening locomotor activity peak and the morning activity peak, respectively (6)(7)(8)(9)(10)(11)(12)(13). E cells include the 5th LNv, dorsal lateral neurons (LNds), and a few dorsal neurons (DN1s).…”
mentioning
confidence: 99%